TINGKAT PLOIDI DAN TIPE REPRODUKSI Dryopteris sparsa DI HUTAN WISATA CANGAR KOTATIF BATU JAWA TIMUR - Siti Zubaidah (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
Study of ploidy level and reproduction type of the fern species Dryopteris sparsa growing in Hutan Wisata Cangar (HWC) Kotatif Batu Jawa Timur and their relationship to the variation of leaf form and size was carried out. Ploidy level was determined based on somatic chromosome number counts by using standard squash methods. Reproduction type was examined by a spore count methods. The morphological characters that examined were the blade length, ratio of basal pinna length to blade length, ratio of stipe length to leaf length and ratio of basal basiscopic pinnule length to basal pinna length. We found that D. sparsa have two forms of ploidy levelreproduction type, there were sexual diploid (2n = 58) and sexual tetraploid (2n = 164). They could be differentiated by the variation of leaf form and size.